Exploring the Impact of Real-Time Monitoring in Incubator Systems: A Study on Android Incu Analyzer and Wireless Technologies - Muntadhar Wahab Razzaq (American Journal of Botany and Bioengineering, 2025)
The objective of the research was to analyse the impact of real-time monitoring in incubator systems by using Incu Analyzer, as a case study object. Incu Analyzer is a small-scale system that is installed into the incubator to enhance incubator’s monitoring capabilities. It can measure temperature and humidity that allows users to monitor it through the internet. The research found that having Incu Analyzer in the incubator would benefit the user to monitor their incubator easily and quickly . Moreover, the result indicates that the real-time monitoring of the incubator can increase the successful rate of the egg hatching process. The highlights of the study indicate the importance of creating better health monitoring devices for incubator system. To summarise, this research found that real-time monitoring of the incubator system can increase the successful rate of the egg hatching process in incubator systems. The rapid progress of incubation technologies in animal agriculture has highlighted the requirement to develop high-quality incubators at an affordable price which can optimally facilitate the incubation process. It is also known that good incubation results are not solely a consequence of the abilities of operators and the nature of the eggs themselves. Incubators equipped with up-to-date and complete supporting instruments can lead one to be more successful in terms of the abilities of operators. To this purpose, the availability of health monitoring devices to support incubators is indispensable. Moreover, in current practices, health monitoring is performed for all the supporting instruments that are used in the incubators mechanised. In view of the quick communication capability between the monitoring devices and the receiving device, wireless technology is considered to be more suitable than conventional monitoring devices which use cables. However, in most cases, the price and infrastructure support of the cable version of the monitoring device are more affordable. Wireless technologies related to incubation processes have developed rapidly in recent years. In general, wireless technology is commonly used in the form of WiFi and GSM. FIFO Technology is widely known to be used as a network interface for many devices such as laptops and smartphones. An advanced mechanism on wireless data transmission is proposed by developing Android-based Incu Analyzer to incubator system, which extract the temperature and humidity data from the incubator system. The Incu Analyzer periodically beam the data from the incubator system to the Remote Incu Analyzer via Bluetooth and then sends the data to the remote user via Wireless game Ultrasonic Frequency Sound. This research is significant because with Incu Analyzer, user can monitor the incubator that operates far away from them. This mechanism can also be used to improve monitoring the health of other supporting instruments on incubator system that are not yet available.